Echa zagłady Ormian w literaturze polskiej - Morawiec, Arkadiusz (Slavia Occidentalis, 2015)
The article contains a catalogue of plots and motifs related to the genocide of the Armenians (committed by the Turks in the years 1915-1923) in Polish literature. The earliest work referring to this crime is Stefan Żeromski’s novel Przedwiośnie (1924), the latest one is Julia Hartwig’s poem Słodka Armenia w trzech przestrzeniach (2007). In Polish literature, the extermination of the Armenians is presented most often in the context of other tragic historical events, including wars and revolutions (Zofia Nałkowska’s Choucas), the extermination of the Jews during World War II (Bohdan Gębarski’s List do starego tureckiego znajomego, Włodzimierz Paźniewski’s Neurosa teutonica) and other acts of genocide (Wiktor Woroszylski’s Zagłada gatunków, Alina Margolis’s Moralność czasu Holokaustu). In communist Poland this tragedy was invoked mainly to enhance the “splendour” of contemporary Soviet Armenia (Igor Sikirycki’s poem Powitanie Armenii, the factual works: Andrzej Mandalian’s Notatki armeńskie, Ryszard Kapuścinski’s Wanik czyli druga Armenia, Monika Warneńska’s Ścieżką na Ararat). Among these works, a special one is Bohdan Gębarski’s Morituri. Opowieść o 1915 r., which is first and foremost a literary (fictionalized) attempt to boost awareness of the Armenian Genocide.